Modern aspects of diagnostics and treatment of H. pylori infection from standpoint of stomach cancer prophylaxis - A. A. Sheptulin; T. L. Lapina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To discuss modern aspects of diagnostics and treatment of H. pylori infection in relation of stomach cancer prophylaxis according to data of oral and poster presentations, delivered at XXVII International workshop of the European Helicobacter Study Group.Summary. The main attention has been given to relation of H. pylori infection to stomach cancer and eradications of infection as a mean of malignancy prevention. Data on relation of H. pylori to other diseases, including non-gastroenterological disorders are presented. Comparative estimation of efficacy of different modes of eradication therapy is given. According to conclusion of the majority of publications and data of meta-analyses, nowadays both bismuth-based and bismuth-free quadrotherapy are considered as the most effective treatment algorithms.Conclusion. For estimation of role of H. pylori infection in development of various diseases, and to improve management of patients further studies are required.